Perspectives on a 'Sit Less, Move More' Intervention in Australian Emergency Call Centres - Michelle Daley; Jen-Kui Maxwell; Josephine Y Chau; Lina Engelen; Sarah Burks-Young; Adrian Bauman; Karen Milton (AIMS Press, 2016)
Background: Prolonged sitting is associated with increased risk of chronic diseases. Workplace programs that aim to reduce sitting time (sit less) and increase physical activity (move more) have targeted desk-based workers in corporate and university settings with promising results. However, little is known about 'move more, sit less' programs for workers in other types of jobs and industries, such as shift workers. This formative research examines the perceptions of a 'sit less, move more' program in an Australian Emergency Call Centre that operates 24 hours per day, 7 days per week. Methods: Participants were employees (N = 39, 72% female, 50% aged 36-55 years) recruited from Emergency Services control centres located in New South Wales, Australia. The 'sit less, move more' intervention, consisting of emails, posters and timer lights, was co-designed with the management team and tailored to the control centre environment and work practices, which already included electronic height-adjustable sit-stand workstations for all call centre staff. Participants reported their perceptions and experiences of the intervention in a self-report online questionnaire, and directly to the research team during regular site visits. Questionnaire topics included barriers and facilitators to standing while working, mental wellbeing, effects on work performance, and workplace satisfaction. Field notes and open-ended response data were analysed in an iterative process during and after data collection to identify the main themes. Results: Whilst participants already had sit-stand workstations, use of the desks in the standing position varied and sometimes were contrary to expectations (e.g, less tired standing than sitting; standing when experiencing high call stress). Participants emphasised the "challenging" and "unrelenting" nature of their work. They reported sleep issues ("always tired"), work stress ("non-stop demands"), and feeling mentally and physically drained due to shift work and length of shifts. Overall, participants liked the initiative but acknowledged that their predominantly sitting habits were entrenched and work demands took precedence. Conclusions: This study demonstrates the low acceptability of a 'sit less, move more' program in shift workers in high stress environments like emergency call centres. Work demands take priority and other health concerns, like poor sleep and high stress, may be more salient than the need to sit less and move more during work shifts.